Effect of Temperature and Protease on The Desalting Process of Scomberoides commersonianus (Talang Queenfish) - Tan Ping Foon; Muhammad Lubowa; Azhar Mat Easa; Shin Yong Yeoh (Journal of Food Innovation, Nutrition, and Environmental Sciences)
This study evaluated the effects of temperature and protease (Alcalase) on the desalting process of salted Talang Queenfish (Scomberoides commersonianus) and the resulting textural and sensory properties of the fish. Salted fish samples were desalted using different temperatures (25°C, 40°C, 60°C, and 80°C) and Alcalase concentrations (1%, 2%, and 3%) at pH 7 and 60°C. The results showed that higher desalting temperatures or increased Alcalase concentrations significantly (p < 0.05) increased salt removal, reducing the salt content in the fish muscle. The addition of Alcalase accelerated the desalting process, reducing desalting time compared to traditional methods. Textural analysis indicated that the fish’s hardness, cohesiveness, and chewiness decreased as desalting temperature and Alcalase concentration increased. Sensory evaluations revealed no significant changes in overall acceptability, with desalting at 60°C and 1% Alcalase yielding the best balance of saltiness and texture. Furthermore, retort-processed salted fish curry prepared from desalted samples maintained favorable sensory properties. These findings suggest that alternative desalting methods using Alcalase and elevated temperatures can enhance desalting efficiency while maintaining product quality.